Outcomes of Mesh Versus Tissue Repair in Emergency Incarcerated Hernia - Muhammad Ali Sumbal, Muhammad Nasir Iqbal, Muhammad Azhar Qureshi, Mariam, Muhammad Akram Dogar, Muhammad Rizwan Saleem, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Emergency incarcerated hernia repair presents a clinical dilemma regarding the safety of mesh usein potentially contaminated fields. This prospective cohort study compared outcomes between mesh and tissue repair in emergency